Pengembangan Pendidikan Profesi Apoteker Untuk Mendukung Eksistensi Apoteker di Apotek - Sukrasno, Sukrasno (UI Scholars Hub, 2008)
Aphothec is a place for pharmacy services especially for pharmacist who dedicates his competency in the community. The policy no pharmacist no service is a strategic policy that has to be supported by all members of Indonesian Pharmacist Association. This policy can only be accomplished if pharmacists produced are equipped with com-petencies that are needed to run an apothec and also supported with adequate motiva-tion. Transformation of senior pharmacist that has been socially established will not give significant impact. To produce competent pharmacist, transformation in educa-tion process especially for pharmacist in the apothec is needed. Transformation must be based on the need of competency and supporting resources. Only with adequate supporting resources, the education process will yield output that match with the demand of formulated competency. As professional practician, new pharmacist has to be able to demonstrate his competency in the apothec. This competency can only be gained through experiences in handling similar activities in the job field. In this scheme, professional pharmacy student has to work in the relevant job field for certain period followed by certification test conducted by certified professional pharmacy edu-cation provider. Only participants that pass the certification test are eligible to hold apothecary (pharmacist) degree and to run an apothec. The education provider can be university by involving certified pharmacist as examiner. This scheme is developed based on the study on the professional pharmacy education scheme implemented in various countries.